Is there a link between androgenetic alopecia and COVID-19? - Zaremba, Bartłomiej; Gorecka, Adrianna; Wieteska, Małgorzata; Raczkiewicz, Przemysław; Stanicki, Paweł (Journal of Education, Health and Sport, 2021)
Introduction and purpose: 20% of COVID-19 cases require hospitalization, with men most often being affected. Current studies indicate a relationship between the incidence and severity of the disease and androgens, including a worse prognosis in patients with androgenetic alopecia. The aim of the study is to analyze the available literature in the Pubmed and Google scholar database in order to find an answer to the question of whether there is a cause-and-effect relationship between androgenetic alopecia and COVID-19. State of knowledge: Male sex hormones, androgen receptors, the presence of substances inducing the development of the inflammatory process and genetic factors are important in the pathogenesis of androgenetic alopecia. It has been noted that androgens are involved in the entry of SARS-CoV-2 into cells and the reduction of the inflammatory response of the body that contribute to the development of the disease. On the one hand, patients hospitalized due to SARS-CoV-2 infection have low levels of male sex hormones, and on the other hand, diseases associated with increased levels of androgens, such as androgenetic alopecia or prostate cancer, are associated with more frequent incidence. Summary: The relationship of androgens to the development of COVID-19 is not clear. Therefore, the relationship of this disease with androgenetic alopecia cannot be directly explained and there is a need for further research.